2017
DOI: 10.1002/2017ja024016
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Altitude Emission of Energetic Neutral Atoms: Multiple Interactions and Energy Loss

Abstract: Low‐altitude emissions (LAEs) are the energetic neutral atom (ENA) signature of ring current ions precipitating along the magnetic field to an altitude of 200–800 km. This altitude region is considered to be “optically thick” because ring current ions undergo multiple charge changing interactions (MCCIs) with Earth's dense oxygen exosphere. While each interaction involves an energy loss of ~36 eV, no prior study has determined the accumulated energy lost by 1–100 keV H+ emerging as LAEs. We have developed a 2‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Analysis of LAEs has also advanced understanding of low‐altitude ion‐neutral interactions. LLera et al () used a novel analytical approximation to a full transport code to study the energy loss experienced by particles in the thick‐target region where LAEs are generated. Precipitating ions undergo multiple charge‐exchanging interactions, and each such interaction incurs an energy penalty of ∼36 eV (Dalgarno, ; Dalgarno & Griffing, ).…”
Section: Scientific Results From 2013 To 2017mentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of LAEs has also advanced understanding of low‐altitude ion‐neutral interactions. LLera et al () used a novel analytical approximation to a full transport code to study the energy loss experienced by particles in the thick‐target region where LAEs are generated. Precipitating ions undergo multiple charge‐exchanging interactions, and each such interaction incurs an energy penalty of ∼36 eV (Dalgarno, ; Dalgarno & Griffing, ).…”
Section: Scientific Results From 2013 To 2017mentioning
confidence: 99%
“…Models are essential to interpreting how the complexities of ion‐neutral interactions produce the low‐altitude ENA signal that TWINS observes. LLera et al () used an analytical approximation to a full transport code to understand the energy loss experienced by ions and neutrals undergoing multiple charge‐exchanging interactions to produce LAEs. With the help of the model, they found that the divergent dipole magnetic field line geometry plays a crucial role in helping ENAs to escape to high altitudes.…”
Section: Scientific Results From 2013 To 2017mentioning
confidence: 99%
“…The LAE distributions for H and O tend to have a smaller energy spread than the HAEs. LAEs may have significant energy loss due to the multiple interactions (LLera et al, ), so care must be taken when comparing the LAEs and HAEs.…”
Section: Observations Of the St Patrick's Day 2015 Stormmentioning
confidence: 99%
“…The ion‐neutral interactions that create LAEs have been studied for two decades using transport codes, analytical models, and numerical inversion methods (Bazell et al, ; Brandt et al, ; Galand et al, ; Galand & Richmond, ; LLera et al, ; Perez et al, ; Roelof, ; Roelof & Skinner, ). The first geospace ENA images contained contributions from LAEs (Roelof, ).…”
Section: Introductionmentioning
confidence: 99%
“…Goldstein et al () reported that isolated substorm injections during the 2015 St. Patrick's Day storm caused LAE spectral cooling by bringing in less energetic ions from the magnetotail. These multiple LAE observational studies have also fostered the development of new analysis tools: energy corrections that convert LAE spectra to ion flux spectra (Bazell et al, ; LLera et al, ), a geometric correction for pixels larger than the LAE source region (Goldstein et al, ), and an analytical model for LAE emissivity (Goldstein et al, ).…”
Section: Introductionmentioning
confidence: 99%